Colegio Santo Domingo Business High School Library a proposed plan for its establishment and development - Cruz, Denise Marie F. (2006)
Even without the DECS Order No. 6, s. 1998, it is inevitable that a school must be able to provide its teachers and students with a sufficient and efficient library. The library is able to help the continuous learning that both the students body and the faculty go through.